Aortic hemodynamic parameters as predictors of incident or deteriorating hypertension during carfilzomib therapy in patients with relapsed multiple myeloma. (14th October 2021) - Laina, A; Georgiopoulos, G; Makris, N; Gavriatopoulou, M; Papanagnou, E; Eleutherakis-Papaiakovou, E; Fotiou, D; Dialoupi, I; Migkou, M; Roussou, M; Terpos, E; Trougakos, I; et al.
Abstract: Background: Carfilzomib (CFZ) improves survival in relapsed/refractory multiple myeloma but is associated with cardiovascular adverse events, among which hypertension is commonly reported. Purpose: To evaluate aortic hemodynamics as possible predictors for CFZ-associated hypertension. Methods: In a prospective study of 48 patients treated with Kd (CFZ 20/56 mg/m 2 and dexamethasone) followed until disease progression or cycle 6 for a median of 10 months, patients underwent peripheral hemodynamic assessment, including applanation tonometry, which allows estimation of aortic blood pressure and arterial wave reflections and assessment of pulse wave velocity, which allows estimation of aortic stiffness. Hemodynamic parameters were examined at baseline and at pre-specified time points before and 24 hours after drug infusion. Results: Thirteen patients (27.1%) developed hypertension or merited more intensive anti-hypertensive treatment (grade I or II: 6.25%, grade III: 20.8%). Patients with new onset or worsening hypertension had increased aortic [130±12.9 mmHg versus 115±16.7 mmHg, p=0.004] and peripheral systolic blood pressure (SBP) [145±15.7 mmHg versus 130±19.5 mmHg, p=0.001] at baseline. Patients distributed at highest tertile of baseline aortic SBP (log-rank test p=0.0001, Figure) or baseline peripheral SBP (log-rank test p=0.002) had significantly higher risk for CFZ associated hypertension as compared to those distributed at lower tertiles. After adjustment for age, gender and baseline hypertension, increased aortic [HR=8.0, 95% CIs 2.4–26.6, p=0.001] and peripheral SBP [HR=4.85, 95% CIs 1.53–15.4, p=0.007] remained significantly associated with hypertension. After adjustment for both baseline peripheral and aortic SBP in the same multivariable core model, aortic SBP was the only independent predictor of the study outcome (p=0.041). Accordingly, baseline aortic SBP was associated with higher discriminative value as compared to peripheral SBP [AUC: 0.819, 95% CIs 0.722–0.916 versus 0.724, 95% CIs 0.570–0.878, respectively]. Further adjustment for all cardiotoxicity risk factors using forced inclusion in non-parsimonious multivariable Cox regression models, revealed that increased aortic and peripheral SBP remained independent predictors of hypertensive events (p<0.05 for both). Conclusion: Baseline aortic hemodynamics are associated with hypertension during CFZ treatment. Aortic SBP at baseline was the strongest predictor of CFZ-associated hypertensive adverse events, suggesting that an initial assessment of aortic blood pressure may facilitate discrimination of patients in need of close monitoring during treatment. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Funding from the Hellenic Foundation for Research and Innovation (HFRI) and the General Secretariat for Research and Technology (GSRT), under grant agreement No [1285].